Peranan Aplikasi My Inspection dalam Aktivitas Operasional Airfield Lighting System di Bandar Udara Internasional Jenderal Ahmad Yani - Semarang - Yusril; Bunahri, Rifqi Raza; Arta, Deddy Novie Citra; Kona, Musri (SKY EAST: Education of Aviation Science and Technology, 2023)
Safety and comfort for aircraft passengers when the aircraft is going to the runway (runway) for take off (take off) or leaving the runway (runway) when finished landing (landing) must pass through a termite road (taxiway), In case In order for aircraft traffic to run smoothly, the structure and geometry of the taxiway plays an important function in the process of moving aircraft from the airport building to the runway or from the runway to the airport building in a short time. The Airfield Lighting System control system or what is usually called a landing visual aid uses a Control Desk which is operated by an Air Traffic Controller (ATC). As technology develops, the use of digital applications is very useful for an Air Traffic Controller. This research uses a qualitative type of research so that the results obtained are that there are fundamental differences in airfield lighting operational activities between the manual recording process and the digital recording process, with manual recording being done one by one, however, if it is done digitally it does not require a lot of human resources (HR), the data obtained is accurate, the risk of data loss is quite small. And the risk of calculation errors is small. Using the My Inspection Officer application within PT. Angkasa Pura 1 (Persero) makes it easier for technicians to record inspections or check the readiness of Ahmad Yani International Airport-Semarang.